Epistemological Framework of Islamic Education Science - Moh. Irmawan Jauhari (Al-Hayat: Journal of Islamic Education, 2017)
A science has an indivisible arrangement with one another. There is epistemology, ontology, and axiology. In a Western perspective, the epistemology of a science there are only two ways to get it. By way of empiricism, or rationalism. So that scientific battle until now berkutat on two things. Islam has a more varied form of epistemology, although in some cases there are indications of similarity with the West. Bayani, burhani, and irfani, is a form of epistemology that is owned by Islam. The presence of these three forms of epistemology should be able to be a bargain for civilization and scientific development today. Because the epistemology of empiricism has no meaningful opponent of rationalism. So the flow of knowledge only flows from the realm of empiricism. Education in Islam plays an important role. With the education of the younger generation is expected to become better in any side. The existence of the design of Islamic education epistemology is expected to be able to print a more powerful Muslim generation in the field of science mastery and hold fast to his religion.